Fighting Inflation More Effectively without Transferring Central Banks' Profits to Banks - Paul De Grauwe; Yuemei Ji (Center for Economic Studies and ifo Institute (CESifo), 2023)
The major central banks now operate in a regime of abundance of bank reserves. As a result, they can only raise the money market rate by increasing the rate of remuneration of bank reserves. This, in turn, leads to large transfers of the central banks' profits (and more) to commercial banks that will become unsustainable and makes the transmission of monetary policies less effective. We propose a two-tier system of reserve requirements that would only remunerate the reserves in excess of the minimum required. This would drastically reduce the giveaways to banks, allow the central banks to maintain their current operating procedures and make monetary policies more effective in fighting inflation.
Keywords: E52; E58; 330; monetary policy; bank reserves; minimum reserve requirements